2022
DOI: 10.25270/wnds/2022.3642
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Platelet-rich Plasma vs Conventional Dressing in the Management of Chronic Diabetic Foot Ulcers

Abstract: Introduction. Diabetic foot ulcers (DFUs) are a major complication of diabetes. Recently, considerable progress has been achieved in techniques that promote wound healing. Autologous platelet-rich plasma (PRP) is one such technique that is gaining popularity. Platelet-rich plasma is thought to stimulate wound healing by releasing growth factors essential for healing. Objective. This research aimed to study the efficacy of PRP in managing chronic DFUs. Materials and Methods. Seventy-two patients with chronic DF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 0 publications
1
34
0
Order By: Relevance
“…Overall in these 13 trials, 85.4% had neuropathic ulcers and 14.6% had ischaemic ulcers (Table 2). Twenty‐eight trials reported the ulcer duration 15,16,18,20,22–24,30–42,44–48,50–52 and 29 trials reported ulcer size at the start of the study 15,16,18,20,22–24,29–40,42–48,50–52 (Table 2). None of the included trials with mixed aetiology DFU reported complete wound healing of neuropathic and ischaemic ulcers separately.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall in these 13 trials, 85.4% had neuropathic ulcers and 14.6% had ischaemic ulcers (Table 2). Twenty‐eight trials reported the ulcer duration 15,16,18,20,22–24,30–42,44–48,50–52 and 29 trials reported ulcer size at the start of the study 15,16,18,20,22–24,29–40,42–48,50–52 (Table 2). None of the included trials with mixed aetiology DFU reported complete wound healing of neuropathic and ischaemic ulcers separately.…”
Section: Resultsmentioning
confidence: 99%
“…Overall 11 trials had a low risk of bias, 15,20,23,32,33,36,39,43,47,48,52 9 had some concerns, 18,29,35,37,40,41,45,50,51 and 11 had a high risk of bias 16,22,24,30,31,34,38,42,44,46,49 (Table 3). In the randomisation process, 22 trials had a low risk of bias 15,16,18,20,23,29,30,32–34,36–39,43,45–48,50,52,53 and 9 had some concerns 22,24,31,35,41,42,44,49,51 . Thirteen trials had a low risk of bias, 15,16,20,22,23,32,33,36,39,43,47,48,52 15 had some concerns 18,24,29–31,34,35,37,41,42,44,45,50,51,53 and 3 had a high risk of bias 38,46,49 in deviation from the intended intervention.…”
Section: Resultsmentioning
confidence: 99%
“…Nowadays, PRP has been applied in clinical trials and is supposed to be a potential treatment for chronic wound treatment. Among these studies, there were two routes of PRP administration found: one constituted injecting PRP around the wound, and the other one constituted wrapping the wound with PRP dressing [ 60 ]. Because of the high risk of subcutaneous injection and the pain of injection, most studies focused on the clinical healing rate and complications of PRP dressings in treating chronic wounds.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of other cell-based treatment strategies have been tested in controlled clinical trials for adjunctive treatment of DFUs, including autologous and allogeneic MSCs derived from bone marrow and adipose tissue [80][81][82], autologous adipose tissue and adipose-derived stromal vascular fraction cells [83,84], autologous platelet-rich plasma [83,[85][86][87][88][89][90], allogeneic platelets [91], autologous skin cells [92], skin allografts [93], and various cell-containing skin substitute products [94][95][96][97][98][99] (for a summary see Additional file 1: Table S15). The reported effects show great variations, ranging from wound surface area reductions and full wound closure ratios within 12-26 weeks that did not significantly differ from the control groups [82,83,85,92] to impressive significant wound surface area reductions from baseline of up to 98% within 80 days [90] and wound closure ratios of up to 100% within 8 weeks [84].…”
Section: Discussionmentioning
confidence: 99%